La encuesta sobre las deudas debidas a los judíos en el arzobispado de Toledo (1493-96). The Survey of Debts Owed to Jews in the Archbishopric of Toledo (1493-1496) - Castaño, Javier (En la España Medieval, 2006)
A detailed analysis of the goods left by the Jews expelled in 1492 debts left uncollected and real estate properties in certain areas of the archbishopric of Toledo, according to the accounts of the royal investigating judges who collected them for the royal coffers: areas of the middle bank of the Jarama, Ocaña and its region, Campiña del Henares, Alcarria, the region of Pastrana. A study of the type of debts and goods, names of the creditor or owner Jews. An explanation for the selective action of the investigating judges in certain areas and regions more than others is provided.